Abu Zayd's Interpretation of the Story of the Prophet Moses: Reading the Prophet's Humanity in a Contextual Hermeneutic Frame - Muzaqky Muthahhari; Khairunnas Jamal; Mochammad Novendri S (Lembaga Yasin AlSys, 2026)
This study investigates Nasr Ḥāmid Abu Zayd’s interpretation of the Qur’anic story of Prophet Moses through the framework of contextual hermeneutics, against the background of traditional Qur’anic exegesis that predominantly emphasizes the miraculous and transcendental aspects of prophethood and tends to portray prophets as infallible and distant figures. The study aims to analyze how Abu Zayd challenges this paradigm by reinterpreting revelation as a historical discourse shaped by human language, socio-political context, and lived struggle. Employing a qualitative textual analysis, the research examines Abu Zayd’s primary works—Mafhūm al-Naṣṣ (The Concept of Text) and Naqd al-Khiṭāb al-Dīnī (Critique of Religious Discourse)—alongside contemporary academic discussions on humanistic and contextual hermeneutics. The findings show that Abu Zayd depicts Moses not as a mythical hero but as a profoundly human figure who fears, doubts, errs, and grows (Qur’ān 28:15–16), thereby foregrounding prophetic experience as ethically charged human struggle rather than static perfection. Through this lens, the Qur’ān emerges as a living dialogue between the divine and the human that continually generates meaning through historical interaction. The study concludes that Abu Zayd’s hermeneutics redefines prophethood in terms of ethical humanity instead of unattainable divine impeccability and offers a liberating, contextually relevant interpretive model for modern Islamic thought, particularly for rethinking asbāb al-nuzūl, contextual tafsīr, and contemporary engagements with prophetic narratives.